Paul in Current Anglophone Scholarship - Wright, N. T. (The expository times, 2012)
Current Anglophone research on Paul has gone in different directions, following the break-up of an older consensus: the ‘new perspective’ and reactions thereto, particularly examining Paul’s relation to scripture and narrative; Paul’s supposedly ‘apocalyptic’ theology; Paul’s relation to the Roman empire; to contemporary philosophy, particularly Stoicism; and substantial explorations of Paul’s socio-historical context. The central task of interpretation, that of historically and theologically coherent exegesis, is more challenging than before but no less exciting.